2023
DOI: 10.3390/ijerph20075361
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Physical Activity and Intrinsic Capacity in Chinese Older Adults and Its Connection to Primary Care: China Health and Retirement Longitudinal Study (CHARLS)

Abstract: Background: In 2015, intrinsic capacity (IC) was proposed by the WHO as a new measure for healthy aging. Evidence has shown that physical activity (PA) benefits the physical and mental health of older adults. However, the association between PA and IC among older adults was not well evaluated or reported. This study aims to investigate the association between PA and general and specific IC among Chinese older adults. Method: The study included individuals aged 60 and above from the China Health and Retirement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Therefore, we considered whether a method that can simultaneously prevent and improve depression and cognitive dysfunction could improve the daily living ability and quality of life of elderly people in our country. Previous studies have shown that appropriate physical activity for elderly people can effectively prevent a decrease in intrinsic capacity, including cognitive function, motor function and mental function [29]. From a physiological point of view, physical activity has a number of benefits, including the prevention of decreased cardiovascular system function, sarcopenia, decreased bone density, increased blood pressure, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we considered whether a method that can simultaneously prevent and improve depression and cognitive dysfunction could improve the daily living ability and quality of life of elderly people in our country. Previous studies have shown that appropriate physical activity for elderly people can effectively prevent a decrease in intrinsic capacity, including cognitive function, motor function and mental function [29]. From a physiological point of view, physical activity has a number of benefits, including the prevention of decreased cardiovascular system function, sarcopenia, decreased bone density, increased blood pressure, etc.…”
Section: Discussionmentioning
confidence: 99%